Islamic student financing securitization (ILMU-Financing) / Mohammed Hariri Bakri, Nurayati Dabas and Shafinar Ismail - Bakri, Mohammed Hariri; Dabas, Nurayati; Ismail, Shafinar (Division of Research and Industry Linkages, 2017)
Security Commission in Malaysia introduced guideline how to issue asset-backed securitization (ABS) in 2001. The securitization is a creative process of raising funds by issuing marketable securities that are backed by future cash flows from revenue producing assets. Until September 2017, ABS represents alternative long-term funding of auto loans, lease, credit cards' receivables and commercial mortgages. We particularly focus herein on the funding of student loans problem, which has not yet been implemented as a securitization process in Malaysia. This work considers the characteristics of Malaysian higher education, suggests a structure for Islamic student loan-backed securitization, and studies the potential of the Islamic securitization process in resolving the problem o f funding for higher education, The innovation in this research is the framework of Islamic student loan-backed securitization. This framework is proposed to create a new and highly graded shariah financial instrument that will benefit the government, investors and the students in Malaysia.